THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON LENOVO LAPTOP CONSUMER PURCHASE DECISIONS IN WONOMULYO DISTRICT, POLEWALI MANDAR REGENCY - Wulan Rahmayanti S; Nur Qamariah S; Nurfitri Ayu Mandasari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The Influence of Product Quality and Price on Consumer Purchase Decisions of Lenovo Laptops in Wonomulyo District, Polewali Mandar Regency. This study aims to determine the effect of product quality and price on consumer purchasing decisions for Lenovo laptops at Kartika Cell, Wonomulyo District, Polewali Mandar Regency. The background of this research is the decline in Lenovo’s sales in Indonesia due to intense competition with other brands such as Asus, Acer, and HP. The method used was quantitative research by distributing questionnaires to 65 respondents who were consumers of Kartika Cell. The data were analyzed using multiple linear regression with the help of SPSS 24. The results showed that product quality had a positive and significant effect on purchasing decisions. In addition, the price variable also had a positive and significant effect on purchasing decisions. Consumers considered that the prices offered were in line with the quality and benefits obtained. Simultaneously, product quality and price had a significant influence with a contribution of 88.1% to purchasing decisions, while the remaining percentage was influenced by other factors not examined in this study.